2017
DOI: 10.17957/ijab/15.0294
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Priming on Emergence, Weed Infestation, Growth and Yield of Wheat Sown under Different Tillage Practices

Abstract: Tillage practices are generally used to prepare seedbed and to control weeds but frequent use of tillage practices accelerate the degradation of soil resources and creates plough pan. However, zero tillage (ZT) has potential to overcome the tillage-induced restrictions and ensure timely wheat planting as well. Moreover, ZT resulted in poor and erratic emergence while seed priming could be used to improve emergence under ZT. Hence this experiment was conducted to evaluate the role of seed priming to improve whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…Results showed that the integrated weed management tools tested in the different countries: provided sufficient weed control without any significant differences in yields, greatly reduced maize reliance on herbicides, and integrated weed management implementation was economically sustainable as no significant differences in gross margin were observed in any country compared to the conventional approach. Similar results were obtained by Hussain et al (2017). Verschwele et al (2016) found that, however, considering the variation of the residual weed density in this study, it is evident that the integrated weed management strategy may result in high weed seed production before harvest and consequently in weed problems in the succeeding crops.…”
Section: Introductionsupporting
confidence: 89%
“…Results showed that the integrated weed management tools tested in the different countries: provided sufficient weed control without any significant differences in yields, greatly reduced maize reliance on herbicides, and integrated weed management implementation was economically sustainable as no significant differences in gross margin were observed in any country compared to the conventional approach. Similar results were obtained by Hussain et al (2017). Verschwele et al (2016) found that, however, considering the variation of the residual weed density in this study, it is evident that the integrated weed management strategy may result in high weed seed production before harvest and consequently in weed problems in the succeeding crops.…”
Section: Introductionsupporting
confidence: 89%
“…Ensuring early and vigorous crop establishment is a key factor in achieving maximum wheat yield under the RW cropping system. Previous results indicated that the seeding rate could be efficiently increased to enhance seed germination and seedling establishment, and thereby improve fertile tiller production ( Shah et al, 2020 ; Hussain et al, 2017 ; Song et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spike length showed significant difference among all treatments however, highest spike length (15.10 cm) was observed in treatment 9 with application of N 3 -160 kg/ha + CCC (0.2%) + Tebuconazole (0.1%). Whereas, spike length (13.83 cm) of treatment 6 with application of N 3 -160 kg/ha + Tebuconazole -0.1% was found to be statistically at par with highest Hussain et al [17] and Ahmad et al [18]. They concluded that spike length of wheat increased significantly with increasing nitrogen levels.…”
Section: Spike Length (Cm)mentioning
confidence: 93%